Primary Ovarian Solid Pseudopapillary Neoplasm With CTNNB1 c.98C>G (p.S33C) Point Mutation. (March 2018) - Singh, Kamaljeet; Patel, Nimesh; Patil, Pallavi; Paquette, Cherie; Mathews, Cara A.; Lawrence, W. Dwayne
Abstract : Ovary is one of the extrapancreatic sites of origin of solid pseudopapillary neoplasm (SPN). Only 9 cases of primary ovarian SPN, 1 with CTNNB1 mutation similar to pancreatic SPN, have been reported in the English literature. We describe the second case of ovarian SPN with confirmed CTNNB1 mutation. A 49-year-old postmenopausal woman presented with a 4.5 cm right ovarian mass. Ovarian mass showed histologic and immunohistochemical features of pancreatic SPN. The ovarian surface was intact and uninvolved. Ki-67 index was low (1%–5%). DNA sequencing of CTNNB1 exon 3 revealed c.98C>G (p.S33C), a well-characterized activating mutation. Our case adds to the growing body of evidence that primary ovarian SPN are phenotypically and genotypically similar to pancreatic SPN.